Development of workplace‐based assessment tools to support postgraduate training of provisionally registered pharmacists in Australia. Issue 4 (6th November 2022) - Maundu, Josephine; Galbraith, Kirsten; Croft, Hayley; Clark, Bronwyn; Kirsa, Sue; Wilkinson, Glenys; Abeyaratne, Carmen
Abstract: The Australian Pharmacy Council (APC) is the national accreditation authority for pharmacy education and training in Australia. In 2020, APC published revised Accreditation Standards and a new Performance Outcomes Framework (POF). The POF details expected performance for pharmacy students at the point of graduation and for pharmacy graduates on completion of postgraduate training. The APC and the pharmacist regulator, the Pharmacy Board of Australia collaborated on a project to develop workplace‐based assessment (WBA) tools for use in assessing performance of pharmacy graduates in the postgraduate training period. The objectives of the project were to; identify and develop an initial suite of WBA tools; develop accompanying guidance and supporting documentation; seek feedback from stakeholders; and pilot the WBA tools in community and hospital settings. The WBA tools were developed through consultative process overseen by a group of education experts (a Technical Working Group) and a governance group. The latter comprising members from the Pharmacy Board and APC. The Technical Working Group agreed on the tools to develop based on an available Intern Year Assessment Blueprint and the tools were then drafted by a consultant. APC held consultative forums and a pilot study to gather feedback from intern pharmacists and preceptors. The project resulted in development of a suite of three types of WBA tools; Entrustable Professional Activities (EPAs), Case Based Discussions (CbD), and In Training Assessment (ITA) activities covering six areas of focus. All types of tools that were initially agreed upon were made available for use. The WBA tools address 15 performance outcomes in the POF. Future direction will involve further evaluation of the tools in diverse practice settings and expansion of the current suite of tools to cover additional performance outcomes.